Surgical site infections after parotidectomy: management and benefits of an antibiotic prophylaxis protocol - MECCARIELLO, G. (Acta Otorhinolaryngol Ital, 2019)
The use of perioperative prophylactic antibiotics in uncontaminated head and neck surgery is still controversial. The aim of this study was to assess the efficacy of an institutional antibiotic prophylactic protocol in preventing surgical site infection after parotidectomy. The medical charts of 448 patients who underwent parotidectomy were reviewed. Patients were divided in two groups according the use of perioperative administration of intravenous cefazolin or post-operative week course of antibiotics. Surgical site infection was registered in 29 (6.5%) cases, 16 (5.7%) within the group before the application of the perioperative protocol and 13 (7.9%) within the antibiotic prophylaxis protocol group. The univariate and multivariate logistic regression analyses showed that predictors for surgical site infection were the amount of drain output ≥ 50 ml in the first post-operative 24 hours (OR: 4.86; 1.59-14.82 95% CI; p < 0.01) and history of a previous parotid acute infection (OR: 13.83; 5.31-36 95% CI; p < 0.01). The majority of post-surgical infections (82%) were treated with intravenous antibiotic therapy. The remnants were treated surgically. Perioperative antibiotic treatment is recommended for patients undergoing parotid gland surgery and intravenous antibiotics during the post-operative course are highly suggested in case of history of previous acute parotid infection and drain output ≥ 50 ml in first 24 hours.